2020
DOI: 10.3390/ijms21165820
|View full text |Cite
|
Sign up to set email alerts
|

Gut-Pancreas-Liver Axis as a Target for Treatment of NAFLD/NASH

Abstract: Non-alcoholic fatty liver disease (NAFLD) represents the most common form of chronic liver disease worldwide. Due to its association with obesity and diabetes and the fall in hepatitis C virus morbidity, cirrhosis in NAFLD is becoming the most frequent indication to liver transplantation, but the pathogenetic mechanisms are still not completely understood. The so-called gut-liver axis has gained enormous interest when data showed that its alteration can lead to NAFLD development and might favor the occurrence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 314 publications
1
40
0
2
Order By: Relevance
“…Although there were no statistically significant differences, which was partly due to the high variation in the expression from mouse-to-mouse, the observed trends suggest that synbiotic yogurt feeding reduced inflammation in the intestinal tissues. Intestinal leakiness and inflammatory signals can pass through the liver and migrate to the pancreas through portal circulation [ 23 ]. Interestingly, we observed increases in leaky gut markers, such as lipopolysaccharide binding protein (LBP) and cluster of differentiation 14 (CD14) antigen, as well as increases in pro-inflammatory markers, such as tumor necrosis factor-alpha (TNF-α), in the liver of control yogurt-fed mice compared to the milk- and synbiotic yogurt-fed groups ( Figure 4 h–j).…”
Section: Resultsmentioning
confidence: 99%
“…Although there were no statistically significant differences, which was partly due to the high variation in the expression from mouse-to-mouse, the observed trends suggest that synbiotic yogurt feeding reduced inflammation in the intestinal tissues. Intestinal leakiness and inflammatory signals can pass through the liver and migrate to the pancreas through portal circulation [ 23 ]. Interestingly, we observed increases in leaky gut markers, such as lipopolysaccharide binding protein (LBP) and cluster of differentiation 14 (CD14) antigen, as well as increases in pro-inflammatory markers, such as tumor necrosis factor-alpha (TNF-α), in the liver of control yogurt-fed mice compared to the milk- and synbiotic yogurt-fed groups ( Figure 4 h–j).…”
Section: Resultsmentioning
confidence: 99%
“…As NAFLD and non-alcoholic stateohepatitis (NASH) are closely related to macro-cardiovascular events and are associated with reduced life expectancy, early and appropriate therapeutic intervention is essential [ 16 ]. However, despite the role of incretin hormones in NAFLD pathogenesis [ 17 ] and various interventions targeting the gut-pancreas-liver axis, in NASH treatment no approved treatment is currently available [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…[9] Several studies have identified bacterial genera, families, and phyla that differ significantly in NAFLD and are implicated in the disease pathogenesis through increased intestinal permeability (i.e., Lachnospiraceae), decreased short chain fatty acids (SCFA) production (i.e., Faecalibacterium), and elevated serum endotoxin production (i.e., Bacteroides, Enterobacteriaceae). [10,11] While lifestyle modification remains the main mode of therapy, [1] still there is an unmet need for new treatments, with natural products being explored as candidates. [12] Mastiha is a natural nutritional supplement based on the dried resinous exudate from stems and branches of the tree Pistacia lentiscus.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] Several studies have identified bacterial genera, families, and phyla that differ significantly in NAFLD and are implicated in the disease pathogenesis through increased intestinal permeability (i.e., Lachnospiraceae), decreased short chain fatty acids (SCFA) production (i.e., Faecalibacterium ), and elevated serum endotoxin production (i.e., Bacteroides , Enterobacteriaceae). [ 10,11 ]…”
Section: Introductionmentioning
confidence: 99%